Some Economic and Administrative Problems that are Stated as Disrupting the Economic Order in Political Books and Divan Poetry - Bilgin, Emrah (Fırat University, 2021)
Many works have been written in the style of advice in the Turkish-Islamic literature. In these written works, advice was given about the procedures on many subjects. One of these issues is about the recommendations on the composition of the economy, which consists of the activities of people such as production, consumption and distribution. In some of the independent works, in which information on the social, political and economic situation of the society is given, there are also important information about the problems related to the economic situation of the state and the solution of these problems. It is known that Yusuf Has Hacip's Kutadgu Bilig, Gelibolulu Mustafa Âlî's Nushatü's-selâtîn or Mawâ'idü'n-nefâ'is fî-kawâ'idi'l-mecâlis and Koçi Bey's treatises such as the important writings included in the politics tradition. there are artifacts. In addition to these works, some other sources, written in the style of advice, expressed the measures to be taken in order to ensure the livelihood of the people entrusted to the administrators and to maintain the state economy. Basically, the problems mentioned in the works are divided into two as those related to the administrative and economical system. In this study, the reasons that cause economic problems and the solutions offered by the authors, who were the intellectuals of the past period, were tried to be examined by taking the advice in the said works into consideration.

Türk-İslâm literatüründe nasihatnâme tarzında pek çok eser kaleme alınmıştır. Yazılan bu eserlerde pek çok konu hakkında usul ve erkâna dair öğütler verilmiştir. Bu konulardan bir tanesi de insanların üretim, tüketim, dağıtım gibi etkinliklerinden oluşan ekonominin tertibi ile ilgili tavsiyeler hakkındadır. Toplumun sosyal, siyasi ve ekonomik durumuna dair bilgiler verilmiş olan kimi müstakil eserde devletin ekonomik durumu ile ilgili sorunlar ile bu sorunların çözümüne dair de önemli bilgiler yer almaktadır. Yûsuf Has Hâcib’in Kutadgu Bilig’i, Gelibolulu Mustafa Âlî’nin Nushatü’s-selâtîn’i veya Koçi Bey’in risâleleri gibi siyâsetnâme geleneği içerisinde yer alan mühim eserler ile nasihat üslubu üzere kaleme alınmış kimi başka kaynaklarda yöneticilere emanet olan halkın geçiminin sağlanması ve devlet ekonomisinin düzenli olabilmesi için alınması gereken tedbirler ifade edilmiştir. Esasta eserlerde bahsi geçen sorunlar, idari ve iktisat sistemi ile ilgili sorunlar olarak ikiye ayrılmıştır. Bu çalışmada da söz konusu eserlerde yer alan nasihatler dikkate alınarak ekonomik sorunları doğuran sebepler ile bu alandaki problemlere karşı geçmiş dönemin aydınları olan müelliflerin verdikleri kimi çözüm önerilerinin incelenmesine gayret edilmiştir.
SİYASETNÂMELERDE VE DİVAN ŞİİRİNDE EKONOMİK DÜZENİ BOZDUĞU BELİRTİLEN BAZI İKTİSADİ VE İDARİ SORUNLAR